Photon-in/photon-out spectroscopy at the I20-scanning beamline at diamond light source. (4th June 2021) - Hayama, Shusaku; Boada, Roberto; Chaboy, Jesús; Birt, Adrian; Duller, Graham; Cahill, Leo; Freeman, Adam; Amboage, Monica; Keenan, Luke; Diaz-Moreno, Sofia
Abstract: A scanning multi-crystal x-ray emission spectrometer to perform photon-in/photon-out spectroscopy at the I20-Scanning beamline at Diamond Light Source is described. The instrument, equipped with three analyzer crystals, is based on a 1 m Rowland circle spectrometer operating in the vertical plane. The energy resolution of the spectrometer is of the order of 1 eV, having sufficient resolving power to overcome the core-hole lifetime broadening of most of the transition metals K -edges. Examples showing the capability of the beamline for performing high energy resolution fluorescence detection x-ray absorption spectroscopy (HERFD-XAS), non-resonant x-ray emission spectroscopy (XES) and resonant x-ray emission spectroscopy are presented. The comparison of the Zn and Mn K -edge HERFD–XANES of ZnO and MnO with ab initio calculations shows that the technique provides enhanced validation of the models by making subtle spectral features more visible.